2021
DOI: 10.1097/md.0000000000023894
|View full text |Cite
|
Sign up to set email alerts
|

Music-based intervention to reduce aggressive behavior in children and adolescents

Abstract: Background: We aimed to evaluate the effect of music-based intervention on the aggressive behavior in children and adolescents, and made a comparison of music medicine and music therapy. Methods: We searched PubMed (MEDLINE), Ovid-Embase, and the Cochrane Central Register of Controlled Trials (CENTRAL) to identify relevant studies. Standardized mean differences (SMDs) were estimated with random-effect model. Results: We included 10 studies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 33 publications
0
8
0
2
Order By: Relevance
“…[ 39 , 40 ] The music therapy group displayed much less hostile behavior than the control group. [ 11 ] Choi et al discovered that music therapy boosts self-worth and reduces hostility. [ 13 ] This study supports earlier studies that suggest music therapy may lessen hostility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 39 , 40 ] The music therapy group displayed much less hostile behavior than the control group. [ 11 ] Choi et al discovered that music therapy boosts self-worth and reduces hostility. [ 13 ] This study supports earlier studies that suggest music therapy may lessen hostility.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that music intervention is helpful in lowering aggression and enhancing self-control in teenagers. [ 11 ] It was also found that music improved pupils’ academic experiences [ 12 ] and children who took part in music intervention showed less aggressive behavior and had higher self-esteem than those who did not. [ 13 ] Music intervention had a greater impact on patients’ aggression and agitation reduction than pharmaceutical interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence is a period of change for developmental and social domains [1] that may be accompanied by behavioral problems such as aggressive behaviors [2]. Aggressiveness among adolescents may constitute concerns for school health and adolescent health [3,4], and it is defined as a behavioral and emotional response that may be distressing for others [5].…”
Section: Introductionmentioning
confidence: 99%
“…El uso de la música ha obtenido resultados saludables recientemente a la hora de reducir problemas de comportamiento psicológico en niños y adolescentes, incluso con efectos más positivos que el uso de fármacos (Ye et al, 2021). En el campo de las emociones, la música ha Máster Universitario en Profesorado Emilio Molina Molina Universidad de Granada Curso 2020 / 2021 sido usada con fines de regulación emocional (Thoma et al, 2012), definida esta por Gross (1998) como: "a process by which individuals influence which emotions they have, when they have them, and how they experience and express their emotions" 1 (p. 275).…”
Section: Justificación Teóricaunclassified
“…De hecho, la música puede producir cambios diferentes en el control del cerebro sobre las emociones, así como aliviar el dolor (Yin, 2021). Se ha demostrado asimismo una mejora significativa en el comportamiento agresivo y un incremento del autocontrol de niños que siguieron una intervención basada en terapia y medicina musical (Ye et al, 2021).…”
Section: Justificación Teóricaunclassified